The Species Composition of the Dendroflora in the Exposition Areas of “Nova Sofiyivka” Park - Porokhniava, Olha; Hrabovyi, Volodymyr; Rumiankov, Yurii; Muzyka, Hryhorii; Kopylova, Tetiana (Banko Janakari, 2026)
The study aimed to determine the species composition of the “Nova Sofiyivka” park and assess the appropriateness of plant selection for creating thematic compositions. The analysis of 9 exhibition zones in the “Nova Sofiyivka” park revealed differences in the species composition across the various areas. The dendroflora of the Entrance Zone plot includes 13 taxa from 5 families. The composition of the Entrance Group plot consists of 9 taxa of woody plants, which belong to 5 families. The species diversity of woody plants in the Fountain Square plot includes 19 taxa from 10 families. The dendroflora of the Regular Garden plot includes 16 taxa from 12 families, the Fairytale Garden plot includes 14 taxa from 8 families, and the Japanese Garden plot includes 68 taxa from 12 families. To createthe dendro-compositions in the Ukrainian Homestead plot, 7 taxa from 7 families are used, in the Dragon Garden plot, 7 taxa from 6 families, and in the Lake plot, 11 taxa from 4 families. The plant compositions on the territory of the “Nova Sofiyivka” park include 112 taxa of woody plants: 49 taxa of deciduous tree species, 47 taxa of deciduous shrubs, 8 taxa of coniferous tree species, and 8 taxa of coniferous shrubs. The research results can be used for planning ethno-compositions and creating recreational areas in urbanized environments.